THE USE OF RECIPROCAL TEACHING TECHNIQUE TO IMPROVE STUDENT’S READING COMPREHENSION TO RECOUNT TEXT - Juliawati, Euis; Sudarsono, Sudarsono; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research was to find out how does reciprocal teaching technique improve student’s reading comprehension of recount text. A classroom action research it was conducted in 3 cycles, each of which consisted of four stages of planning, acting, observing and reflecting. The subject of research was XI-IPS 1 students of SMAS Mujahidin Pontianak in Academic Year 2018/2019. Observation and measurement technique were used as the technique of data collecting. Observation checklist, field notes, and reading comprehension test were used as the tools of data collecting. Reciprocal teaching technique could improve student’s reading comprehension through predicting, questioning clarifying, and summarizing. In predicting, the students could understand the content of passage about what will happen next in the text. In constructing the questions, the students could use 5W1H formula to help them creating the questions. Through clarifying, the students clarified their understanding of the text by identifying the linguistics feature of recount text. Through summarizing, the students summarized the text using their own language. The data from reading comprehension test showed that students reading comprehension improved from cycle to cycle. The student’s mean score improved from 45.67 and then improved to 60.51 and up to 81.60.  Key words: Classroom Action Research, Reading Comprehension, Recount                                 Texts, Reciprocal Teaching Technique